Proposal for a comprehensive security manual for the Ecuadorian public sector - Galarza, Máximo Ortega; Altamirano, Rodrigo; Avilés, Moisés Nikolay Trujillo; Rodas, Pablo Patricio Naranjo; Coloma, Máximo Leonid Ortega; Coloma, Kathrina Samira Ortega (Seven Editora, 2024)
Institutions today have to be safe, healthy places where collective and individual well-being prevails, particularly for those who provide their personal and professional services in public institutions. It is mandatory at this juncture to seek and apply certain security instruments that allow us to optimize and guarantee the lives of the people who make up the Public Institutionality. DOI:https://doi.org/10.56238/sevened2024.018-068